Efeitos de instruções, treino de relato verbal e treino de automonitoração sobre o seguimento de regras nutricionais em crianças com obesidade ou sobrepeso - MARTINS, Lana Cristina Cardoso de Oliveira (Universidade Federal do Pará, 2014)
Obesity is a chronic illness defined as the accumulation of abnormal or excessive fat that can cause harm to people’s health. It has become necessary to fight it and intervene in favour of its prevention, especially among children. The literature in this field indicates that, in general, interventions only with children or caregivers, or both, show favorable results. This study assessed the effects of instructions, verbal report training (VRT) and self-monitoring training (ST), applied with and without the participation of the primary caregiver, on following nutritional rules in obese or overweight children. The participants were two children (9 and 11 years old) and their primary caregivers. The setting was an outpatient clinic in the Psychology department of a university hospital. The patients’ medical records, an initial interview form, the Parenting Style Inventory (PSI), a second interview form, dietary recall, an informative manual on obesity and healthy eating habits, a knowledge test, a nutritional counseling protocol for children, a self-monitoring protocol, a guide for analysis of the self-monitoring protocol, toys and games and a final interview form were used. The collection procedure occurred in 10 sessions distributed in approximately 15 weeks and consisted of medical records analysis; interview at the outpatient clinic with the caregiver and the child for signing the Free and Informed Consent Form, application of the initial interview form and the PSI; participants’ inclusion in one of two conditions (Condition 1, only the child present [P1]; Condition 2, both the child [P2] and his/her primary caregiver [C2] were present); application of the second interview form followed by the dietary recall use (Baseline 1 [BL1]); application of the informative manual on obesity and healthy eating habits and the knowledge test; VRT (Baseline 2 [BL2]); ST; follow-up interview and final interview. As for the effects of instructions, the results indicate that P1 maintained the same classification on all items, while P2 improved his/her performance in the items knowledge and nutritional orientation follow and C2 showed improvement in the knowledge about obesity at the end of the study. Adherence to diet scores obtained by P2 were higher than those obtained by P1 in all phases of the study. Comparing the mean obtained by both participants in BL1 and BL2, an increase of 39.77 % was observed indicating clinically significant change after intervention. The combination of variables in this study was favorable on the participants’ repertoire extension in relation to eating behavior, having the subject himself as reference throughout the study. The results suggest that there is higher effectiveness when children and caregivers are the target of intervention.